Café Marketing Strategy Analysis in The Covid-19 Pandemic - Sitorus, Nova Bernedeta; Juliana, Juliana; Maleachi, Sandra; Djakasaputra, Arifin; Prabowo, Gunawan (International Journal of Social and Management Studies, 2021)
Entering the pandemic period, S.T. made several strategic changes. ALi Jakarta includes outlets in SetiaBudi to continue innovating and attracting buyers to shop because of the PSBB and PPKM, which have made profits from the food and beverage industry relatively low. S.T.ALi carried out several marketing strategies during the pandemic. ST, ALi will focus on marketing instant products that are easy to enjoy at home because buyers will spend more time at home. 1-litre bottle packaging and care products are one of the breakthroughs that are widely discussed in Indonesia. This 1-litre bottle packaging can also be more easily marketed with the emergence of new drink types and flavours that are continuously updated regularly within a certain period. In this study, there are two problem formulations: (1) how is the marketing strategy of S.T. Ali Jakarta outlets during the Covid-19 pandemic (2) how does S.T. carry out the marketing mix. Ali outlets during the Covid-19 pandemic. The purpose of this study is to analyze the marketing strategy of S.T. Ali Jakarta outlets during the Covid-19 pandemic and to explore the marketing mix carried out by S.T.ALi outlets during the Covid-19 pandemic. This research is qualitative. The object used in this research is a cafe named S.T. ALi Jakarta, which has an Australian-style concept. Data collection techniques include surveys, participation, observation, interviews, field notes, and analytical memos, elicitation of documents, personal experiences, and participation in follow-up studies. Some data collection techniques are the same as "methodological trade," which can be varied according to the researcher's interests. The study results found that the marketing strategy was done through digital marketing, website facilities, and social media marketing, namely Instagram. Each uploaded content varies and includes important and interesting information to provide the latest promotions to followers and potential customers. The S.T. cafe carries out the marketing mix. ALi Jakarta following the concept of eight Marketing Mixes (8P) has been executed quite well, starting from a variety of products with a uniquely Australian theme, prices according to quality, placement of the right outlets with the location of the majority of the target market, attractive and profitable promotions, skilled human resources. trained and professional to improve the good image, quality packaging with beautiful and durable designs, structured system management, to partnerships that can support and provide every need needed by the organization Keywords — Strategy, Marketing, Restaurant, Hospitality